Analysis of the economic impacts of the legal framework for distributed generation law 14,300/22 on photovoltaic systems - Sá Barrêto do Rosário Pinheiro dos Santos, Brendeson; Sanca Sanca, Huilman; dos Santos Junqueira, Caio Marco (Latin American Journal of Energy Research, 2025)
In January 2022, Law No. 14,300 (Legal Framework for Distributed Generation) introduced significant changes to the compensation system and rules for consumers with distributed generation (DG). This study evaluates the impacts of the new law on micro and mini photovoltaic generation plants, covering the generation process, regulatory changes, and case studies with feasibility analysis based on scenarios from REN No. 482/2012 and Law No. 14,300, considering both upfront and financed payments. The results show that, for residential microgeneration, Law No. 14,300 increased the payback period and reduced financial indicators, such as net present value (NPV), internal rate of return (IRR), and return on investment (ROI), especially in financing scenarios. Conversely, mini-generation experienced improvements in these indicators, highlighting advantages for larger-scale projects, which became more attractive and economically viable.
Keywords: Photovoltaic system; Distributed generation; REN 482/2012; Law 14.300; Economic viability